Jakobs Rolle in der Genesis - Fischer, Georg 1954- (2003)
Jacob plays a crucial role within the book of Genesis. His figure contains programmatic, synthetic and definitive traits. His second name, Israel, points to a special relevance for those called by the same name: the people and the believing community. The two phases of his life show a clear direction towards reconciliation and an emphasis on this theme. This is further confirmed by a series of reversals in which Jacob, either suffering or actively engaged, solves conflicts or problems of his forefathers and the primeval history. These relations with past events indicate that the book of Genesis may have been conceived as a whole, with the figure of Jacob / Israel as its keystone and conclusion.
Keywords: Jakob -- Biblische Person; Bibel; Versöhnung